2014
DOI: 10.1088/0004-637x/783/1/6
|View full text |Cite
|
Sign up to set email alerts
|

HiRes DECONVOLVEDSPITZERIMAGES OF 89 PROTOSTELLAR JETS AND OUTFLOWS: NEW DATA ON THE EVOLUTION OF THE OUTFLOW MORPHOLOGY

Abstract: To study the role of protosellar jets and outflows in the time evolution of the parent cores and the protostars, the astronomical community needs a large enough data base of infrared images of protostars at the highest spatial resolution possible, to reveal the details of their morphology. Spitzer provides unprecedented sensitivity in the infrared to study both the jet and outflow features, however its spatial resolution is limited by its 0.85m mirror. Here we use a high resolution deconvolution algorithm, "Hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
67
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 57 publications
15
67
2
Order By: Relevance
“…outflow by using the parabolic model considering the inclination angle. The results quantitatively supports the trend suggested previously (Arce & Sargent 2006;Seale & Looney 2008;Velusamy et al 2014). Figure 11 shows a semi-log plot of v 0 /DR 0 versus dynamical timescale t dyn .…”
Section: Comparison With Other Sourcessupporting
confidence: 89%
See 2 more Smart Citations
“…outflow by using the parabolic model considering the inclination angle. The results quantitatively supports the trend suggested previously (Arce & Sargent 2006;Seale & Looney 2008;Velusamy et al 2014). Figure 11 shows a semi-log plot of v 0 /DR 0 versus dynamical timescale t dyn .…”
Section: Comparison With Other Sourcessupporting
confidence: 89%
“…If the emission in the L′ band is weakened by the outflow cavity wall, the brightness on the two sides of the protostar depends on the distribution of matter in the outflow cavity, and the brightness asymmetry cannot constrain the direction of the inclination. Very recently, Velusamy et al (2014) reported that the Spitzer 3.6 μm HiRes deconvolved image shows the brightness asymmetry of the outflow cavity in the vicinity of the protostar that is opposite to that reported by Tobin et al (2008Tobin et al ( , 2010. The result by Velusamy et al (2014) seems consistent with the positive inclination angle that we found in this study.…”
Section: Direction Of the Outflowsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies have found a correlation between outflow opening angle and protostellar age, where older sources have wider outflows (Arce & Sargent 2006). However, more recent infrared scattered-light studies have come to a variety of conclusions, suggesting that the relationship between outflow opening angle and age is not yet certain (Seale & Looney 2008;Velusamy et al 2014;Booker et al 2017;Hsieh et al 2017). …”
Section: Shaping Of the Magnetic Field By The Wide-angle Low-velocitmentioning
confidence: 99%
“…X-ray emission from protostellar jets was first reported by Pravdo et al (2001), who detected an X-ray source coincident with HH 2 that was not associated with any other galactic or extragalactic source (see Velusamy et al 2014). Later, Favata et al (2002) detected X-ray emission from HH 154, a jet associated with the protostar L1551 IRS5 in the Taurus Molecular Cloud (see also Bally et al 2003;Bonito et al 2004Bonito et al , 2011Favata et al 2006).…”
Section: Introductionmentioning
confidence: 86%